Aviation composite material resistant to lightning damage and preparation method thereof
By using high-strength carbon fiber and electroless silver-plated diamond-like graphite skeletons such as epoxy resin, graphite honeycomb sandwich layer, thermoplastic microcapsules and conductive films in aviation composite materials, the problem of lightning damage caused by composite materials is solved, and a high conductivity, self-healing and lightweight lightning damage-resistant composite materials are achieved.
Patent Information
- Application Number
- CN202310380613.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-11
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-04-11
AI Technical Summary
The existing composite material structures in the aerospace field are prone to lightning damage, causing fuselage erosion, puncture, wrinkle, peeling and breakage, seriously threatening the safe operation of the aircraft.
A composite panel consisting of high-strength carbon fiber and epoxy resin filled with electroless silver-plated diamond-like graphite skeletons, and a graphite honeycomb sandwich layer and thermoplastic microcapsules are added therebetween, combining conductive films and C/C-SiC composite fasteners to form a lightning-strike damage-resistant aerospace composite material.
It improves the overall conductivity and current carrying capacity of the composite material, enhances the lightweight properties of the material, realizes an electric-thermal self-repair structure, effectively repairs panels and graphite honeycomb cracks impacted by lightning strikes, extends the service life of the material, and reduces the impact of lightning strikes on the fasteners.
Smart Images

Figure CN116160724B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aviation composite materials, and in particular relates to an aviation composite material resistant to lightning strike damage, and also relates to a preparation method of the aviation composite material resistant to lightning strike damage. Background Art
[0002] Carbon fiber resin-based composite materials have the characteristics of lightweight, high specific strength, high specific modulus, designability and integration. They are the most widely used common materials in the fields of aerospace, national defense and military industry. Their application range and dosage in load-bearing components such as aircraft fuselages and wings have become important indicators for measuring the advancement of aircraft. However, composite structures are frequently struck by lightning during service. Statistical data show that an aircraft is struck by lightning once every 1,000 hours of flight on average, and almost once a year in areas with frequent thunderstorms. When an aircraft is struck by lightning, a strong lightning arc current enters the interior of the composite laminate to generate a large amount of Joule heat, causing ablation damage such as melting, vaporization, and pyrolysis of resin and carbon fiber. Under the combined action of high temperature, high-pressure shock waves and electromagnetic forces of lightning strikes, mechanical damage such as fiber breakage and delamination occurs in the composite material, causing the fuselage of the aircraft to melt, pierce, wrinkle, peel off and break, ultimately reducing the structural mechanical strength, destroying the aircraft body structure, and even causing a lightning strike crash, seriously threatening the safe operation of the aircraft. Therefore, the present invention provides an aviation composite material resistant to lightning damage and a preparation method thereof to solve the problem that composite structures in the existing aerospace field are easily damaged by lightning strikes. Summary of the invention
[0003] The purpose of the present invention is to provide an aviation composite material resistant to lightning damage, thereby solving the problem that the existing materials are easily damaged by lightning.
[0004] Another object of the present invention is to provide a method for preparing an aviation composite material resistant to lightning strike damage.
[0005] The technical solution adopted by the present invention is: an aviation composite material resistant to lightning damage, comprising two layers of carbon fiber composite panels, graphite honeycomb sandwich layers are adhered between the carbon fiber composite panels by conductive adhesive films, thermoplastic microcapsules injected with polyethylene-methacrylic acid copolymer are built into the gaps of the honeycomb sandwich, and the surface of the carbon fiber composite panel is equipped with C / C-SiC composite fasteners.
[0006] Another technical solution adopted by the present invention is: a method for preparing an aviation composite material resistant to lightning damage, which is specifically implemented according to the following steps:
[0007] Step 1. Take a carbon fiber composite panel and place it on the bottom layer;
[0008] Step 2. Lay a conductive adhesive film on the bottom carbon fiber composite panel;
[0009] Step 3. placing a single-hole regular hexagonal graphite honeycomb sandwich layer on the conductive adhesive film, and injecting thermoplastic microcapsules into the honeycomb gaps;
[0010] Step 4. Lay a conductive adhesive film on the graphite honeycomb sandwich layer;
[0011] Step 5. Take another carbon fiber composite panel and place it on the top layer to form a stacking structure;
[0012] Step 6. Place the stacked structure in an oven and bake it into shape;
[0013] Step 7. Punch a circular hole on the surface of the solidified material, and install the C / C-SiC composite material annular groove rivet fastener in the hole.
[0014] Another aspect of the present invention is also characterized in that:
[0015] In step 6, the pressure in the oven is 0.5MPa-0.8MPa, the baking temperature is 130°C-150°C, and the baking time is 1.5h-2h.
[0016] The preparation steps of carbon fiber composite panels are as follows:
[0017] Step 1. Evenly mix liquid bisphenol epoxy resin, phenolic epoxy resin and curing agent in a mass ratio of 10:10:1 to prepare a pre-curing mixed liquid;
[0018] Step 2. Add natural graphite powder to a dry ball mill and grind it thoroughly to obtain fine and uniform graphite powder, and place the ground powder in a selective laser sintering molding machine to prepare a diamond-like structure graphite skeleton blank, and then place the graphite skeleton blank in an oven for curing and molding;
[0019] Step 3. Prepare a silver nitrate aqueous solution, and add a sodium hydroxide solution with a volume of 1% of the silver nitrate aqueous solution, then add concentrated ammonia water, stir until the solution is transparent, and finally add appropriate amounts of glucose and tartaric acid to the mixed solution to prepare a silver plating solution, and immerse the solidified diamond-like graphite skeleton blank into the silver plating solution, let it stand at room temperature, take it out and dry it, so as to obtain a chemically silver-plated diamond-like graphite skeleton;
[0020] Step 4. placing the chemically silver-plated diamond-like graphite skeleton in step 3 into the pre-cured mixed solution in step 1 to obtain an epoxy resin filling material;
[0021] Step 5. Use a hot press curing molding method to wrap the epoxy resin filling material on the high-strength carbon fiber bundle to obtain a carbon fiber composite material panel.
[0022] The specific preparation steps of thermoplastic microcapsules are as follows:
[0023] Step 1. injecting polyethylene-methacrylic acid copolymer particles into a dry ball mill and grinding them into tiny particles with a diameter of about 200 μm to obtain microcapsule core materials;
[0024] Step 2. Select a low melting point thermoplastic material and heat it until it becomes a transparent viscous liquid, and store it in a mold;
[0025] Step 3. Disperse the microcapsule core material in the molten thermoplastic material to form an emulsified dispersion, and atomize the emulsified dispersion into fine droplets in a dry hot air flow through an atomizing device, so that the thermoplastic material outside the core material evaporates, dries and solidifies to form thermoplastic microcapsules.
[0026] The specific preparation steps of the conductive adhesive film are as follows:
[0027] Step 1. Wipe the nylon mesh with alcohol and dry it, then clean it with tin chloride solution and hydrochloric acid, wash the cleaned nylon mesh with distilled water, and activate it with palladium chloride, boric acid and sodium hypophosphite respectively;
[0028] Step 2. Prepare a silver nitrate aqueous solution, and add a sodium hydroxide solution with a volume of 1% of the silver nitrate aqueous solution, then add concentrated ammonia water, stir until the solution is transparent, and finally add appropriate amounts of glucose and tartaric acid to the mixed solution to prepare a silver plating solution, and immerse the sensitized and activated nylon mesh in the silver plating solution, react at room temperature for 1 hour, and then take it out and dry it;
[0029] Step 3. Hot-press the high-temperature conductive silver glue and the nylon mesh treated in step 2 into a film, place the hot-pressed conductive adhesive film between two sandblasted metal molds, and cure it in an oven.
[0030] In step 3, the pressure of the oven is 0.3MPa-0.5MPa, the baking time is 2h-2.5h, and the baking temperature is 160℃-180℃.
[0031] In step 1, the concentration of the tin chloride solution is 15 g / L-20 g / L, the sensitization time is 10 min-15 min, the activation time of palladium chloride and boric acid is 10 min-15 min, and the activation time of sodium hypophosphite is 30 min-40 min.
[0032] The beneficial effects of the present invention are:
[0033] (1) The composite material panel of the present invention is composed of high-strength carbon fiber and epoxy resin filled with chemically silver-plated diamond-like graphite skeleton, and has high electrical conductivity;
[0034] (2) The graphite honeycomb sandwich layer of the present invention enhances the electrical conductivity of the material in the overall thickness direction while making the material as a whole more lightweight;
[0035] (3) The thermoplastic microcapsules of the present invention are injected with polyethylene-methacrylic acid copolymer and dispersed in the pores of the graphite honeycomb to form an electrothermal self-repairing structure, which can effectively repair the panels and graphite honeycomb cracks impacted by lightning and improve the service life of the material;
[0036] (4) The C / C-SiC composite fastener of the present invention is a component for connecting composite materials to aircraft. Compared with metal fasteners, its material properties are similar to those of composite materials, which reduces the probability of lightning directly acting on the fasteners, reduces the problems of resin base ablation around the fasteners, carbon fiber bundle breakage, and fastener shedding caused by lightning strikes, and improves the service life of the material;
[0037] (5) The conductive adhesive film of the present invention is used for bonding composite material panels and graphite honeycomb cores. Its high electrical conductivity can effectively reduce interlaminar damage of the composite material under lightning strikes. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 is a flow chart of the preparation of the aviation composite material resistant to lightning strike damage in Example 1 of the present invention;
[0039] Figure 2 This is a flow chart of the preparation of a carbon fiber composite material panel in Example 1 of the present invention. DETAILED DESCRIPTION
[0040] The present invention is described in detail below in conjunction with specific implementation modes and accompanying drawings.
[0041] The method for preparing the lightning-damage-resistant aviation composite material provided by the present invention is specifically implemented according to the following steps:
[0042] Step 1. Take a carbon fiber composite panel and place it on the bottom layer; the carbon fiber composite panel is made of high-strength carbon fiber and epoxy resin hot press curing molding filled with chemically silver-plated diamond-like graphite skeleton, which improves the conductivity of the panel in the thickness direction and increases the conductivity and current carrying capacity of the overall panel;
[0043] Step 2. Lay a conductive adhesive film on the bottom carbon fiber composite panel;
[0044] Step 3. Place a single-hole regular hexagonal graphite honeycomb sandwich layer on the conductive film, and inject thermoplastic microcapsules into the honeycomb gaps; the graphite honeycomb sandwich layer is formed by regularly arranging and connecting regular hexagonal open-hole graphite cylinders; the conductive film is composed of an electrical adhesive and a nylon braided mesh, wherein the surface of the nylon braided mesh is silver-plated;
[0045] Step 4. Lay a conductive adhesive film on the graphite honeycomb sandwich layer;
[0046] Step 5. Take another carbon fiber composite panel and place it on the top layer to form a stacking structure;
[0047] Step 6. placing the stacked structure in an oven to bake it into shape;
[0048] Step 7. Punch a circular hole on the surface of the solidified material, and install a C / C-SiC composite ring groove rivet fastener in the hole. The C / C-SiC composite fastener is a ring groove rivet composed of a carbon fiber reinforcement phase and a resin carbon matrix introduced with SiC ceramics.
[0049] Example 1
[0050] Method for preparing aviation composite materials resistant to lightning damage, such as Figure 1 As shown, the specific implementation steps are as follows:
[0051] Step 1. Take a 200mm×100mm×0.25mm carbon fiber composite panel and place it on the bottom layer;
[0052] The preparation steps of carbon fiber composite material panel are as follows: Figure 2 As shown:
[0053] Step 1. Weigh liquid bisphenol epoxy resin, phenolic epoxy resin and curing agent in a mass ratio of 10:10:1, set the collector-type constant temperature heating magnetic stirrer to 120°C for preheating for 5 minutes, pour the weighed liquid bisphenol epoxy resin into a flask, place the beaker on a magnetic stirrer and stir for 3 minutes, add the weighed phenolic epoxy resin, continue stirring until it is dissolved and presents a uniform system, cool the collector-type constant temperature heating magnetic stirrer to 100°C, add the curing agent, continue stirring and dissolving until it is a uniform system, and prepare a pre-cured mixed solution;
[0054] Step 2. Weigh 100-mesh natural graphite powder with a mass of 30% of the mass of the pre-cured mixed liquid, add it to a dry ball mill and grind it thoroughly to obtain fine and uniform graphite powder, transfer the ground powder to a selective laser sintering molding machine, and quickly prepare a diamond-like graphite skeleton blank. Then, preheat the oven to 180°C, put the diamond-like graphite skeleton blank in, keep it warm for 30 minutes, and then cool it to room temperature to solidify it. Then, carbonize the graphite skeleton blank in a vacuum carbonization furnace to make a diamond-like graphite skeleton preform;
[0055] Step 3. Weigh a certain amount of silver nitrate reagent to prepare a 25 g / L silver nitrate aqueous solution, add a 2 mol / L sodium hydroxide solution of 1-2% of the volume of the silver nitrate aqueous solution, and continue stirring, then add concentrated ammonia water and stir at the same time until the solution is clear and transparent, and finally add a small amount of glucose and tartaric acid to the solution, stir to a uniform system to prepare a silver plating solution, immerse the diamond-like graphite skeleton preform in the silver plating solution, stand at room temperature for reaction for 1 hour, then take out and dry, to obtain a chemically silver-plated diamond-like graphite skeleton;
[0056] Step 4. placing the chemically silver-plated diamond-like graphite skeleton in step 3 into the pre-cured mixed solution in step 1, mixing and stirring at 120° C. with a magnetic stirrer until a uniform system is obtained, and cooling at room temperature to obtain an epoxy resin filling material;
[0057] Step 5. Use a hot press curing molding method to wrap the epoxy resin filling material on the T700 grade high-strength carbon fiber bundle, and demold it after hot pressing and curing to obtain a 0.25 mm thick fiber composite material panel.
[0058] Step 2. Lay a 200 mm × 100 mm conductive adhesive film on the bottom carbon fiber composite panel;
[0059] The specific preparation steps of the conductive adhesive film are as follows:
[0060] Step 1. After wiping the nylon mesh with alcohol and drying it, it was sensitized and cleaned with 20g / L tin chloride solution and hydrochloric acid respectively, and the sensitization time was 10min. After washing the cleaned nylon mesh with distilled water, it was activated with palladium chloride, boric acid and sodium hypophosphite respectively, and the activation time of palladium chloride and boric acid was 10min, and the activation time of sodium hypophosphite was 30min.
[0061] Step 2. Prepare a silver nitrate aqueous solution, and add a sodium hydroxide solution with a volume of 1% of the silver nitrate aqueous solution, then add concentrated ammonia water, stir until the solution is transparent, and finally add appropriate amounts of glucose and tartaric acid to the mixed solution to prepare a silver plating solution, and immerse the sensitized and activated nylon mesh in the silver plating solution, react at room temperature for 1 hour, and then take it out and dry it;
[0062] Step 3. Heat-press the YC-03 high-temperature conductive silver glue with the nylon mesh treated in step 2 at 90°C and 5MPa to form a film. Place the heat-pressed conductive adhesive film between two sandblasted metal molds and fix it in an oven at a temperature of 180°C and a pressure of 0.3MPa for 2.5 hours to cure it.
[0063] Step 3. Place a regular hexagonal graphite honeycomb sandwich layer with a single hole size of 4 mm in side length, 4 mm in height, and 0.5 mm in wall thickness on the conductive film, and inject thermoplastic microcapsules into the honeycomb gaps;
[0064] The specific preparation steps of thermoplastic microcapsules are as follows:
[0065] Step 1. Inject Nucrel 925 polyethylene-methacrylic acid copolymer particles into a dry ball mill and grind them into tiny particles with a diameter of about 200 μm to obtain microcapsule core materials;
[0066] Step 2. Select a low melting point thermoplastic material including but not limited to polyethylene, polystyrene, polypropylene, and ethylene-vinyl acetate copolymer and place it in a 150° C. heating device for 3 minutes until it becomes a transparent viscous liquid, and place it in a mold for storage;
[0067] Step 3. The microcapsule core material is dispersed in the molten thermoplastic material to form an emulsified dispersion, and the emulsified dispersion is atomized into fine droplets in a dry 100°C hot air flow through an atomizing device, so that the thermoplastic material outside the core material evaporates, dries and solidifies to form 220μm thermoplastic microcapsules.
[0068] Step 4. Lay a 200mm×100mm conductive adhesive film on the graphite honeycomb sandwich layer;
[0069] Step 5. Take another 200mm×100mm×0.25mm carbon fiber composite panel and place it on the top layer to form a stacking structure;
[0070] Step 6. Place the stacked structure in an oven at a temperature of 150° C. and fix it at a pressure of 0.5 MPa for 2 hours to form;
[0071] Step 7. Punch a circular hole with an inner diameter of 10 mm on the surface of the solidified material, and install a C / C-SiC composite material annular groove rivet fastener in the hole.
[0072] Example 2
[0073] The preparation method of the aviation composite material resistant to lightning damage is specifically implemented according to the following steps:
[0074] Step 1. Take a 200mm×100mm×0.25mm carbon fiber composite panel and place it on the bottom layer;
[0075] The preparation steps of carbon fiber composite panels are as follows:
[0076] Step 1. Weigh liquid bisphenol epoxy resin, phenolic epoxy resin and curing agent in a mass ratio of 10:10:1, set the collector-type constant temperature heating magnetic stirrer to 120°C for preheating for 5 minutes, pour the weighed liquid bisphenol epoxy resin into a flask, place the beaker on a magnetic stirrer and stir for 3 minutes, add the weighed phenolic epoxy resin, continue stirring until it is dissolved and presents a uniform system, cool the collector-type constant temperature heating magnetic stirrer to 100°C, add the curing agent, continue stirring and dissolving until it is a uniform system, and prepare a pre-cured mixed solution;
[0077] Step 2. Weigh 100-mesh natural graphite powder with a mass of 30% of the mass of the pre-cured mixed liquid, add it to a dry ball mill and grind it thoroughly to obtain fine and uniform graphite powder, transfer the ground powder to a selective laser sintering molding machine, and quickly prepare a diamond-like graphite skeleton blank. Then, preheat the oven to 180°C, put the diamond-like graphite skeleton blank in, keep it warm for 30 minutes, and then cool it to room temperature to solidify it. Then, carbonize the graphite skeleton blank in a vacuum carbonization furnace to make a diamond-like graphite skeleton preform;
[0078] Step 3. Weigh a certain amount of silver nitrate reagent to prepare a 25 g / L silver nitrate aqueous solution, add a 2 mol / L sodium hydroxide solution of 1-2% of the volume of the silver nitrate aqueous solution, and continue stirring, then add concentrated ammonia water and stir at the same time until the solution is clear and transparent, and finally add a small amount of glucose and tartaric acid to the solution, stir to a uniform system to prepare a silver plating solution, immerse the diamond-like graphite skeleton preform in the silver plating solution, stand at room temperature for reaction for 1 hour, then take out and dry, to obtain a chemically silver-plated diamond-like graphite skeleton;
[0079] Step 4. placing the chemically silver-plated diamond-like graphite skeleton in step 3 into the pre-cured mixed solution in step 1, mixing and stirring at 120° C. with a magnetic stirrer until a uniform system is obtained, and cooling at room temperature to obtain an epoxy resin filling material;
[0080] Step 5. Use a hot press curing molding method to wrap the epoxy resin filling material on the T700 grade high-strength carbon fiber bundle, and demold it after hot pressing and curing to obtain a 0.25 mm thick fiber composite material panel.
[0081] Step 2. Lay a 200 mm × 100 mm conductive adhesive film on the bottom carbon fiber composite panel;
[0082] The specific preparation steps of the conductive adhesive film are as follows:
[0083] Step 1. After wiping the nylon mesh with alcohol and drying it, it was sensitized and cleaned with 15g / L tin chloride solution and hydrochloric acid respectively. The sensitization time was 15min. After washing the cleaned nylon mesh with distilled water, it was activated with palladium chloride, boric acid and sodium hypophosphite respectively. The activation time of palladium chloride and boric acid was 15min, and the activation time of sodium hypophosphite was 40min.
[0084] Step 2. Prepare a silver nitrate aqueous solution, and add a sodium hydroxide solution with a volume of 1% of the silver nitrate aqueous solution, then add concentrated ammonia water, stir until the solution is transparent, and finally add appropriate amounts of glucose and tartaric acid to the mixed solution to prepare a silver plating solution, and immerse the sensitized and activated nylon mesh in the silver plating solution, react at room temperature for 1 hour, and then take it out and dry it;
[0085] Step 3. Heat-press the YC-03 high-temperature conductive silver glue with the nylon mesh treated in step 2 at 90°C and 5MPa to form a film. Place the heat-pressed conductive adhesive film between two sandblasted metal molds and cure it in an oven at 160°C and 0.5MPa for 2 hours.
[0086] Step 3. Place a regular hexagonal graphite honeycomb sandwich layer with a single hole size of 4 mm in side length, 4 mm in height, and 0.5 mm in wall thickness on the conductive film, and inject thermoplastic microcapsules into the honeycomb gaps;
[0087] The specific preparation steps of thermoplastic microcapsules are as follows:
[0088] Step 1. Inject Nucrel 925 polyethylene-methacrylic acid copolymer particles into a dry ball mill and grind them into tiny particles with a diameter of about 200 μm to obtain microcapsule core materials;
[0089] Step 2. Select a low melting point thermoplastic material including but not limited to polyethylene, polystyrene, polypropylene, and ethylene-vinyl acetate copolymer and place it in a 150° C. heating device for 3 minutes until it becomes a transparent viscous liquid, and place it in a mold for storage;
[0090] Step 3. The microcapsule core material is dispersed in the molten thermoplastic material to form an emulsified dispersion, and the emulsified dispersion is atomized into fine droplets in a dry 100°C hot air flow through an atomizing device, so that the thermoplastic material outside the core material evaporates, dries and solidifies to form 220μm thermoplastic microcapsules.
[0091] Step 4. Lay a 200mm×100mm conductive adhesive film on the graphite honeycomb sandwich layer;
[0092] Step 5. Take another 200mm×100mm×0.25mm carbon fiber composite panel and place it on the top layer to form a stacking structure;
[0093] Step 6. Place the stacked structure in an oven at a temperature of 130° C. and fix it at a pressure of 0.8 MPa for 1.5 hours to form;
[0094] Step 7. Punch a circular hole with an inner diameter of 10 mm on the surface of the solidified material, and install a C / C-SiC composite material annular groove rivet fastener in the hole.
[0095] Example 3
[0096] The preparation method of the aviation composite material resistant to lightning damage is specifically implemented according to the following steps:
[0097] Step 1. Take a 200mm×100mm×0.25mm carbon fiber composite panel and place it on the bottom layer;
[0098] The preparation steps of carbon fiber composite panels are as follows:
[0099] Step 1. Weigh liquid bisphenol epoxy resin, phenolic epoxy resin and curing agent in a mass ratio of 10:10:1, set the collector-type constant temperature heating magnetic stirrer to 120°C for preheating for 5 minutes, pour the weighed liquid bisphenol epoxy resin into a flask, place the beaker on a magnetic stirrer and stir for 3 minutes, add the weighed phenolic epoxy resin, continue stirring until it is dissolved and presents a uniform system, cool the collector-type constant temperature heating magnetic stirrer to 100°C, add the curing agent, continue stirring and dissolving until it is a uniform system, and prepare a pre-cured mixed solution;
[0100] Step 2. Weigh 100-mesh natural graphite powder with a mass of 30% of the mass of the pre-cured mixed liquid, add it to a dry ball mill and grind it thoroughly to obtain fine and uniform graphite powder, transfer the ground powder to a selective laser sintering molding machine, and quickly prepare a diamond-like graphite skeleton blank. Then, preheat the oven to 180°C, put the diamond-like graphite skeleton blank in, keep it warm for 30 minutes, and then cool it to room temperature to solidify it. Then, carbonize the graphite skeleton blank in a vacuum carbonization furnace to make a diamond-like graphite skeleton preform;
[0101] Step 3. Weigh a certain amount of silver nitrate reagent to prepare a 25 g / L silver nitrate aqueous solution, add a 2 mol / L sodium hydroxide solution of 1-2% of the volume of the silver nitrate aqueous solution, and continue stirring, then add concentrated ammonia water and stir at the same time until the solution is clear and transparent, and finally add a small amount of glucose and tartaric acid to the solution, stir to a uniform system to prepare a silver plating solution, immerse the diamond-like graphite skeleton preform in the silver plating solution, stand at room temperature for reaction for 1 hour, then take out and dry, to obtain a chemically silver-plated diamond-like graphite skeleton;
[0102] Step 4. placing the chemically silver-plated diamond-like graphite skeleton in step 3 into the pre-cured mixed solution in step 1, mixing and stirring at 120° C. with a magnetic stirrer until a uniform system is obtained, and cooling at room temperature to obtain an epoxy resin filling material;
[0103] Step 5. Use a hot press curing molding method to wrap the epoxy resin filling material on the T700 grade high-strength carbon fiber bundle, and demold it after hot pressing and curing to obtain a 0.25 mm thick fiber composite material panel.
[0104] Step 2. Lay a 200 mm × 100 mm conductive adhesive film on the bottom carbon fiber composite panel;
[0105] The specific preparation steps of the conductive adhesive film are as follows:
[0106] Step 1. After wiping the nylon mesh with alcohol and drying it, it was sensitized and cleaned with 18g / L tin chloride solution and hydrochloric acid respectively. The sensitization time was 13min. After washing the cleaned nylon mesh with distilled water, it was activated with palladium chloride, boric acid and sodium hypophosphite respectively. The activation time of palladium chloride and boric acid was 13min, and the activation time of sodium hypophosphite was 35min.
[0107] Step 2. Prepare a silver nitrate aqueous solution, and add a sodium hydroxide solution with a volume of 1% of the silver nitrate aqueous solution, then add concentrated ammonia water, stir until the solution is transparent, and finally add appropriate amounts of glucose and tartaric acid to the mixed solution to prepare a silver plating solution, and immerse the sensitized and activated nylon mesh in the silver plating solution, react at room temperature for 1 hour, and then take it out and dry it;
[0108] Step 3. Heat-press the YC-03 high-temperature conductive silver glue with the nylon mesh treated in step 2 at 90°C and 5MPa to form a film. Place the heat-pressed conductive adhesive film between two sandblasted metal molds and fix it in an oven at a temperature of 170°C and a pressure of 0.4MPa for 2.2 hours to cure it.
[0109] Step 3. Place a regular hexagonal graphite honeycomb sandwich layer with a single hole size of 4 mm in side length, 4 mm in height, and 0.5 mm in wall thickness on the conductive film, and inject thermoplastic microcapsules into the honeycomb gaps;
[0110] The specific preparation steps of thermoplastic microcapsules are as follows:
[0111] Step 1. Inject Nucrel 925 polyethylene-methacrylic acid copolymer particles into a dry ball mill and grind them into tiny particles with a diameter of about 200 μm to obtain microcapsule core materials;
[0112] Step 2. Select a low melting point thermoplastic material including but not limited to polyethylene, polystyrene, polypropylene, and ethylene-vinyl acetate copolymer and place it in a 150° C. heating device for 3 minutes until it becomes a transparent viscous liquid, and place it in a mold for storage;
[0113] Step 3. The microcapsule core material is dispersed in the molten thermoplastic material to form an emulsified dispersion, and the emulsified dispersion is atomized into fine droplets in a dry 100°C hot air flow through an atomizing device, so that the thermoplastic material outside the core material evaporates, dries and solidifies to form 220μm thermoplastic microcapsules.
[0114] Step 4. Lay a 200mm×100mm conductive adhesive film on the graphite honeycomb sandwich layer;
[0115] Step 5. Take another 200mm×100mm×0.25mm carbon fiber composite panel and place it on the top layer to form a stacking structure;
[0116] Step 6. Place the stacked structure in an oven at a temperature of 140° C. and fix it at a pressure of 0.7 MPa for 1.7 hours to form;
[0117] Step 7. Punch a circular hole with an inner diameter of 10 mm on the surface of the solidified material, and install a C / C-SiC composite material annular groove rivet fastener in the hole.
[0118] The method for preparing the lightning-damage-resistant aviation composite material of the present invention prepares a lightning-damage-resistant composite material with high conductivity, self-repairability and lightness, so as to solve the problem that the carbon fiber composite material in the prior art is easily damaged by lightning.
Claims
1. An aviation composite material resistant to lightning damage, characterized in that: The invention comprises two layers of carbon fiber composite material panels, wherein graphite honeycomb sandwich layers are bonded between the carbon fiber composite material panels via conductive adhesive films, thermoplastic microcapsules injected with polyethylene-methacrylic acid copolymer are embedded in the honeycomb sandwich gaps, and the surface of the carbon fiber composite material panels is equipped with C / C-SiC composite material fasteners.
2. The method for preparing the lightning-damage-resistant aviation composite material according to claim 1, characterized in that: Follow the steps below to implement it: Step 1. Take a carbon fiber composite panel and place it on the bottom layer; Step 2. Lay a conductive adhesive film on the bottom carbon fiber composite panel; Step 3. placing a single-hole regular hexagonal graphite honeycomb sandwich layer on the conductive adhesive film, and injecting thermoplastic microcapsules into the honeycomb gaps; Step 4. Lay a conductive adhesive film on the graphite honeycomb sandwich layer; Step 5. Take another carbon fiber composite panel and place it on the top layer to form a stacking structure; Step 6. placing the stacked structure in an oven to bake it into shape; Step 7. Punch a circular hole on the surface of the solidified material, and install the C / C-SiC composite material annular groove rivet fastener in the hole.
3. The method for preparing the lightning-damage-resistant aviation composite material according to claim 2, characterized in that: In step 6, the pressure in the oven is 0.5 MPa-0.8 MPa, the baking temperature is 130° C.-150° C., and the baking time is 1.5 h-2 h.
4. The method for preparing the lightning-damage-resistant aviation composite material according to claim 2, characterized in that: The steps for preparing the carbon fiber composite material panel are as follows: Step 1. Evenly mix liquid bisphenol epoxy resin, phenolic epoxy resin and curing agent in a mass ratio of 10:10:1 to prepare a pre-curing mixed liquid; Step 2. Add natural graphite powder to a dry ball mill and grind it thoroughly to obtain fine and uniform graphite powder, and place the ground powder in a selective laser sintering molding machine to prepare a diamond-like structure graphite skeleton blank, and then place the graphite skeleton blank in an oven for curing and molding; Step 3. Prepare a silver nitrate aqueous solution, and add a sodium hydroxide solution with a volume of 1% of the silver nitrate aqueous solution, then add concentrated ammonia water, stir until the solution is transparent, and finally add appropriate amounts of glucose and tartaric acid to the mixed solution to prepare a silver plating solution, and immerse the solidified diamond-like graphite skeleton blank into the silver plating solution, let it stand at room temperature, take it out and dry it, so as to obtain a chemically silver-plated diamond-like graphite skeleton; Step 4. placing the chemically silver-plated diamond-like carbon structure graphite skeleton in a pre-curing mixed liquid to obtain an epoxy resin filling material; Step 5. Use a hot press curing molding method to wrap the epoxy resin filling material on the high-strength carbon fiber bundle to obtain a carbon fiber composite material panel.
5. The method for preparing the lightning-damage-resistant aviation composite material according to claim 2, characterized in that: The specific preparation steps of the thermoplastic microcapsules are as follows: Step 1. injecting polyethylene-methacrylic acid copolymer particles into a dry ball mill and grinding them into tiny particles with a diameter of about 200 μm to obtain microcapsule core materials; Step 2. Select a low melting point thermoplastic material and heat it until it becomes a transparent viscous liquid, and store it in a mold; The low melting point thermoplastic material includes one of polyethylene, polystyrene, polypropylene, and ethylene-vinyl acetate copolymer; Step 3. Disperse the microcapsule core material in the molten thermoplastic material to form an emulsified dispersion, and atomize the emulsified dispersion into fine droplets in a dry hot air flow through an atomizing device, so that the thermoplastic material outside the core material evaporates, dries and solidifies to form thermoplastic microcapsules.
6. The method for preparing the lightning-damage-resistant aviation composite material according to claim 2, characterized in that: The specific preparation steps of the conductive adhesive film are as follows: Step 1. After wiping the nylon mesh with alcohol and drying it, it is sensitized and cleaned with tin chloride solution and hydrochloric acid respectively. After washing the sensitized and cleaned nylon mesh with distilled water, it is activated with palladium chloride, boric acid and sodium hypophosphite respectively. Step 2. Prepare a silver nitrate aqueous solution, and add a sodium hydroxide solution with a volume of 1% of the silver nitrate aqueous solution, then add concentrated ammonia water, stir until the solution is transparent, and finally add appropriate amounts of glucose and tartaric acid to the mixed solution to prepare a silver plating solution, and immerse the sensitized and activated nylon mesh in the silver plating solution, react at room temperature for 1 hour, and then take it out and dry it; Step 3. Hot-press the high-temperature conductive silver glue and the treated nylon mesh into a film, place the hot-pressed conductive adhesive film between two sandblasted metal molds, and cure it in an oven.
7. The method for preparing a lightning-damage-resistant aviation composite material according to claim 6, characterized in that: In step 3, the pressure of the oven is 0.3MPa-0.5MPa, the baking time is 2h-2.5h, and the baking temperature is 160°C-180°C.
8. The method for preparing the lightning-damage-resistant aviation composite material according to claim 6, characterized in that: In the step 1, the concentration of the tin chloride solution is 15 g / L-20 g / L, the sensitization time is 10 min-15 min, the activation time of palladium chloride and boric acid is 10 min-15 min, and the activation time of sodium hypophosphite is 30 min-40 min.
Citation Information
Patent Citations
Preparation method of carbon fiber / graphene / epoxy resin prepreg and carbon fiber composite material
CN105968718A
Composite sandwich structure and method of producing and repairing the same
JP2002225210A
Cited By
Lightning-stroke-resistant glass fiber fabric tubular composite material and preparation method and application thereof
CN121105486A